Social Studies Education, Digital Inequality, and Socio-Economic Justice: Narratives from Senior High Schools in Ternate City - Ni'matuz Zuhroh; Aniek Rahmaniah; Mujtahid Mujtahid; Samsul Susilawati; Ulfi Andrian Sari; Sri Nur Rahmi (International Journal of Educational Narratives, 2026)
Background. Digital transformation presents both opportunities and challenges for education in Indonesia, particularly in Eastern Indonesia, including Ternate City. This region faces a persistent digital divide characterized by limited access to digital devices, uneven internet connectivity, and low digital literacy among teachers and students, which negatively affects learning quality, student engagement, and the development of 21st-century competencies such as critical thinking, collaboration, and digital literacy. Purpose. This qualitative study aimed to explore how Social Studies education can contribute to reducing socio-economic inequality and strengthening social inclusion in the context of digital transformation in education. Method. This study employed a qualitative approach, including observations, in-depth interviews, and surveys, to examine the implementation of social studies learning in senior high schools in Ternate City. Results. Findings reveal that social studies education continues to face significant obstacles, including unequal access to digital tools, limited connectivity, and insufficient integration of local content. However, IPS learning has potential to bridge digital and socioeconomic gaps through contextualized content, project-based learning, digital literacy enhancement, and fostering social awareness and economic justice. Effective implementation relies on equitable digital infrastructure, teacher competence in digital pedagogy, and policies responsive to social vulnerabilities. Conclusion. Integrating local wisdom and digital technology enables students to develop analytical, communication, and problem-solving skills while understanding their community’s socio-economic realities.